Field reports summer 1999, Hank Zaletel - Zaletel, Hanket al (1999)
An annotated list of birds sighted by Hank Zaletel. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of summer 1999. Epson - sheet feed